Rekonstruksi Jiwa Peserta Didik dalam Perspektif Pendidikan Hadits - Rinah Rinah; Azni Aisyah; Bainar Bainar; Syukri Syukri (Akhlak : Jurnal Pendidikan Agama Islam dan Filsafat, 2024)
This article aims to explain the hadith about how an educator develops the soul of student Ini the view of the hadith of the propeth muhammad SAW. Every student has the right to obtain knowledge in order to develop the potential that each student has, so that this potential can be developed in character formation and instilling the spirit that student should have. The research we use is a qualitative research method in the nature of library research, where the main object we use are primary and secondary book which produce descriptive data so as to produce the data contained in the int research text. The result of this research are several ways to build student's souls from a hadith perspective. In the hadith that we researched, there is several education that need's to be given to student. Apart from that, manners must also be taught to student. Because this is important in building the soul of student.